2016
DOI: 10.1074/jbc.m116.724153
|View full text |Cite
|
Sign up to set email alerts
|

Topology and Structure/Function Correlation of Ring- and Gate-forming Domains in the Dynamic Secretin Complex of Thermus thermophilus

Abstract: Secretins are versatile outer membrane pores used by many bacteria to secrete proteins, toxins, or filamentous phages; extrude type IV pili (T4P); or take up DNA. Extrusion of T4P and natural transformation of DNA in the thermophilic bacterium Thermus thermophilus requires a unique secretin complex comprising six stacked rings, a membrane-embedded cone structure, and two gates that open and close a central channel. To investigate the role of distinct domains in ring and gate formation, we examined a set of del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…The N3 domain abuts the periplasmic base of the inner β-barrel formed by GATE1 and GATE2 (Figs. 4 , 5 ) and has been demonstrated through mutagenesis to be essential for secretin oligomerization 35 , 40 , 41 . N3 belongs to the family of small mixed α/β domains we previously termed ring building motifs 4 (RBMs) which have been observed in numerous ring forming components from different secretion systems.…”
Section: Resultsmentioning
confidence: 99%
“…The N3 domain abuts the periplasmic base of the inner β-barrel formed by GATE1 and GATE2 (Figs. 4 , 5 ) and has been demonstrated through mutagenesis to be essential for secretin oligomerization 35 , 40 , 41 . N3 belongs to the family of small mixed α/β domains we previously termed ring building motifs 4 (RBMs) which have been observed in numerous ring forming components from different secretion systems.…”
Section: Resultsmentioning
confidence: 99%
“…The particle images on the grid and the 2D class averages ( Figure 1 ) show the typical rod shape of T. thermophilus PilQ ( Burkhardt et al, 2011 ; Salzer et al, 2016 ). The complex has a C-terminal secretin domain, which inserts into the OM, and six N-terminal domains that form six stacked rings N0 to N5, which were found to extend deeply into the periplasm ( Burkhardt et al, 2011 ; Gold et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies we discovered a unique secretin (PilQ) complex in the thermophilic bacterium Thermus thermophilus, which is essential for natural transformation and extrusion of type IV pili ( Friedrich et al, 2002 ; Schwarzenlander et al, 2009 ). We showed that T. thermophilus PilQ contains a thermostable C-terminal secretin domain and an exceptionally long N-terminal tail of six stacked rings (N0-N5) ( Burkhardt et al, 2011 ; 2012 ; Salzer et al, 2016 ). Furthermore, we determined the in situ structure of the entire T4PS machinery by cryo-electron tomography (cryo-ET) in the piliated and unpiliated state, revealing conformational changes of the N-terminal ring-forming domains ( Gold et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…for pilus extrusion and function but are dispensable for natural transformation (Burkhardt et al, 2012;Salzer et al, 2016a). The structural features together with the unprecedented length (34 nm) of the secretin complex suggests that the PilQ complex spans the entire cell periphery, thereby mediating DNA transport across the OM and periplasmic space in a single step, which might be beneficial for DNA uptake in high temperature environments.…”
Section: Natural Competencementioning
confidence: 99%